Asuhan Kebidanan Pada Ibu Hamil Dengan Hipertensi Gestasional Di PMB Nurhayati Wilayah Kerja Puskesmas Air Tiris - Indriani, Novita; Apriyanti, Fitri (Evidence Midwifery Journal, 2024)
Gestational hypertension is one of the problems during pregnancy. Pregnant women with gestational hypertension can experience adverse effects for themselves and their fetuses, such as intrauterine growth restriction (IUGR), intrauterine fetal death (IUFD), preterm labor, placental abruption, and organ failure. The objective of this research is to provide midwifery care for pregnant women with gestational hypertension at PMB Nurhayati in the working area of Air Tiris Health Center from June 4 to June 11, 2024. The results of the case study provided to Mrs. N, with eight home visits, showed that her blood pressure before care was 142/99 mmHg and after receiving care, her blood pressure decreased to 128/90 mmHg. The midwifery care provided included health education about a hypertension diet, therapy by recommending the mother read the Qur'an, and giving the mother cucumber juice mixed with sweet oranges twice a day for seven days. Based on the care provided to Mrs. N, a 28-year-old G2P1AOH1, it was found that her blood pressure decreased, and her complaints were resolved. In conclusion, the care provided was well implemented. It is hoped that pregnant women with gestational hypertension and the general public can increase their knowledge of pregnancy, particularly regarding the knowledge and management of gestational hypertension